To the thursday seminar group
Someone in the thursday seminar group questioned the approach in the last part of 2.24 d where I (in the expression inside the square root) move (1/sigma^2) from the denominator to inside the summation in the nominator.
There are two steps:
1) Apply the rule of complex fractions (norsk: brudden br?k) on the expression inside the square root. (a/b)/(c/d)=(ad/bc). Here a=sum(Y_i^2) b=sigma^2 c=(n-1) and d=1. Alternatively: multiply with 1/sigma^2 in both the nominator and the denominator
Thus: sqrt((sum(Y_i^2)/(sigma^2*(n-1))=sqrt((sum(Y_i^2)/sigma^2)/(n-1))
2. Apply the rule of a sum with a constant first: csum(x)=sum(cx) so I can put sigma inside the summation.
sqrt((sum(Y_i^2/sigma^2))/(n-1))
Published Feb. 6, 2014 3:24 PM